Circulating adhesion molecules and associations with HbA1c, hypertension, nephropathy, and retinopathy in the Treatment Options for type 2 Diabetes in Adolescent and Youth study. Issue 6 (2nd July 2020) - Tryggestad, Jeanie B.; Shah, Rachana D.; Braffett, Barbara H.; Bacha, Fida; Gidding, Samuel S.; Gubitosi‐Klug, Rose A.; Shah, Amy S.; Urbina, Elaine M.; Levitt Katz, Lorraine E.; ,
Abstract: Background: The Treatment Options for type 2 Diabetes in Adolescent and Youth study, a randomized clinical trial of three treatments for type 2 diabetes (T2DM) in youth, demonstrated treatment failure (defined as sustained HbA1c ≥8%, or inability to wean insulin after 3 months after acute metabolic decomposition) in over half of the participants. Given that binding of mononuclear cells to vascular endothelium, initiated by cellular adhesion molecules and chemokines, is an early step in vascular injury, we sought to evaluate (a) changes in cellular adhesion molecule levels during the trial; (b) effect of diabetes treatment; and (c) association of markers with HbA1c, hypertension, hypercholesterolemia, nephropathy, and retinopathy. Methods: Participants (n = 515 of 699) that had baseline assessment of adhesion molecules (monocyte chemoattractant protein‐1 [MCP‐1], vascular cell adhesion marker [VCAM], intercellular adhesion marker [ICAM], and E‐Selectin) and at least one other assessment, measured at month 12, 24, or 36, were included. Results: Over 1 to 3 years, significant increases in MCP‐1 and decreases in VCAM (both P < .0001) concentrations were found; however, no significant interactions were identified with treatment group for any molecule. For every 1% increase in HbA1c, ICAM increased by 1.8%, VCAM by 1.5%, and E‐selectin by 6.8% (all P < .0001). E‐selectin increased by 3.7% and 4.2% for every 10 mm Hg increase in systolic and diastolic blood pressure, respectively (both P < .0001). ICAM was 10.2% higher and E‐selectin was 15.5% higher in participants with microalbuminuria (both P < .01). There was no significant association of adhesion molecule levels with retinopathy. Conclusion: Concentrations of cellular adhesion molecules rise with increasing HbA1c in youth with T2DM, and are associated with blood pressure and microalbuminuria, markers of vascular injury.